Over‐investment or risk mitigation? Corporate social responsibility in Asia‐Pacific, Europe, Japan, and the United States. Issue 2 (8th January 2018) - Utz, Sebastian
Abstract: We study the relationship of corporate social responsibility (CSR) and the distribution of stock returns for an international sample. Firms with a high level of CSR generally exhibit superior stock price synchronicity in the markets of Europe, Japan, and the United States. In particular, we identify optimal levels of CSR to minimize idiosyncratic risk for each region. Moreover, CSR has a mitigating effect on crash risk in Europe and the United States. In contrast, firms from the Asia‐Pacific region display CSR over‐investment followed by a higher crash risk. This appears to be a consequence of globalization, which forces firms from Asia‐Pacific to overinvest in CSR to adapt western standards.